Twin trouble - David, Luke.; Goldberg, Barry, 1960-; Goldberg, Barry, 1960-; Nickelodeon (Firm). (New York: Simon Spotlight/Nickelodeon, 1999)
Lil and Phil are twins that are separated by Betty because they are fighting all the time and they realize that they miss each other while separated.
"Nickelodeon."
"Based on the TV series Rugrats created by Arlene Klasky, Gabor Csupo, and Paul Germain as seen on Nickelodeon"--T.p. verso.
1 8 11 13 15 21 23
Keywords: Separation anxiety -- Juvenile fiction; Rugrats (Fictitious characters) -- Juvenile fiction; Aggressiveness -- Juvenile fiction; Twins -- Juvenile fiction; Babies -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction